The Theory of Lapse of Contract in Civil Law Analytical Study - Ouda, Hussam (Journal of Legal Sciences, 2026)
One of the fundamental features of contract theory in general is its continuous development in accordance with the needs of society and individuals. A prominent recent manifestation of this development recently is the emergence of the theory of lapse of Contract within the amendments to the French Civil Code of 2016. The main objective of stipulating this theory was to address cases in which a contract loses an essential element of its components after it has been properly formed, or when one of the contracts that make up the contractual group is dissolved. Despite the stipulation of this theory in the French Civil Code, its modern nature has led to ambiguity surrounding many of its aspects, such as its concept, its name, and its distinction from other theories and legal situations. Moreover, the French legislator has not resolved the debate on some of its issues, which requires proposing appropriate solutions or weighing the solutions proposed. Therefore, in this study, we will try to explore this theory in light of what has been written by jurisprudence and approved by the French judiciary regarding it. We will define its concept, clarify the dividing lines between it and other legal theories, discuss the names that have been put forward regarding it, explain what is meant by the basic elements whose disappearance leads to the of lapse of Contract and its conditions, and the extent to which it is related to the issue of retroactive effect.